Bayah Natural Zeolites to Upgrade the Quality of Bio Crude Oil from Empty Fruit Bunch Pyrolysis - Irawan, Anton; Bindar, Yazid; Kurniawan, Teguh; Alwan, Hafid; Rosid, Rosid; Fauziah, Nisa Aina (Journal of Engineering and Technological Sciences, 2021)
Currently, the fuel oil for transportation and industry is produced mostly from fossil fuels. Because fossil fuels are a limited resource, biomass could be an alternative resource. Empty fruit bunch (EFB) is biomass waste from fresh fruit bunch processing in palm oil mills. EFB can be converted to bio-crude oil through pyrolysis at temperatures from 400 to 600 °C. The quality of bio-crude oil must be upgraded due to its high oxygen content. Esterification of bio-crude oil potentially improves the quality of bio-crude oil by using zeolite as catalyst. The purpose of this research was to investigate the properties of Bayah natural zeolites for upgrading the quality of bio-crude oil from EFB pyrolysis. Bayah natural zeolite was activated using various NaOH concentrations. Characterization of the natural zeolites was performed by using X-ray diffraction (XRD), scanning electron microscope-energy dispersive X-ray (SEM-EDX), and nitrogen physisorption. The optimum ratio of Si/Al of the modified Bayah natural zeolites was 3.91. The surface area of the parent was initially 19 m2/g and increased significantly to 150 m2/g after treatment with 0.4 M NaOH solution. The application of the activated zeolites for bio-crude oil esterification successfully decreased the total acid number.